Banana starch and molecular shear fragmentation dramatically increase structurally driven slowly digestible starch in fully gelatinized bread crumb. (15th February 2019) - Roman, Laura; Gomez, Manuel; Hamaker, Bruce R.; Martinez, Mario M.
Highlights: Starch digestion was studied in bread containing native and extruded banana starch. A dramatic reduction of banana starch molecular weight was reached during extrusion. A fivefold SDS increase was attained with the inclusion of extruded banana starch. DSC results in crumb showed the creation of slowly digested supramolecular structures. Native and extruded banana starch did not worsen consumer's global acceptability. Abstract: The role of native (NB) and extruded (EB) banana starch, and a 1:1 native:extruded banana starch composite (MB), in slowing down the starch digestibility of bread crumb and crust was investigated. During extrusion, the molecular weight of banana starch was reduced from 2.75 × 10 8 to 4.48 × 10 6 g/mol (HPSEC-MALS-RI). Results showed a slowly digestible starch (SDS) increase from 1.09% (control) to 4.2, 6.6, and 7.76% in NB, MB and EB crumbs (fully gelatinized), respectively. DSC data attributed this occurrence to the formation of supramolecular structures upon storage involving amylopectin branches (especially those from fragmented amylopectin in EB). The hedonic sensory test showed no differences in overall liking between MB, EB and control, validating feasibility of including banana in the formulation. For the first time, this study shows a molecular size reduction as a strategy to manufacture selected starches that result in highly gelatinized baked products rich in structurally driven SDS.